A portable database of adverse reactions and drug interactions with radiopharmaceuticals. - Gómez Perales, Jesús Luis; Martínez, Ana Agudo (Journal of Nuclear Medicine Technology, 2013)
Our objective was to develop a software application that allows us to easily manage a portable database of information on radiopharmaceutical interactions with drugs or other agents and on radiopharmaceutical adverse effects. Methods: The application was developed and compiled with a commercially available data management system and programming language. All data entered into the database came from the scientific literature and were accompanied by their bibliographic references. Results: We developed the database, which we have called Datinrad. To date, it contains 275 drug interactions and 44 records of adverse reactions to radiopharmaceuticals. Conclusion: Datinrad contains all the information published to date on drug-radiopharmaceutical interactions and adverse effects of radiopharmaceuticals and allows users to introduce new data from future publications. The collection of these data and their easy availability to all nuclear medicine personnel will be useful in the recognition of a possible adverse reaction or drug interaction that may alter the radiopharmaceutical biodistribution and lead to a misdiagnosis. This open-access database application is available free of charge in both English and Spanish at www.radiopharmacy.net.